Analysis of the Influence of Clinical Governance on Physician Job Satisfaction at RSUD Teungku Peukan Kab. Southwest Aceh in 2023 - Yenni Sandra Dewi; Asriwati Asriwati; Masnely Lubis (Universitas Ibn Khaldun Bogor, 2024)
This study highlights the importance of physician job satisfaction in the context of health care quality. Modern hospitals must not only comply with regulations, but also uphold high standards to meet patient expectations. Factors such as management, clinical governance, and work environment influence physician job satisfaction. This study aims to investigate whether management factors, especially clinical governance, have an impact on the job satisfaction of doctors at Teuku Pekan Hospital, Southwest Aceh Regency in 2023. A cross-sectional method was used by collecting data through questionnaires to 33 doctors who work at home. the pain. The results of the analysis show that the majority of respondents consider management effectiveness, such as communication and strategy, to be quite effective. However, there are areas that are still less effective, such as risk and resource management. The majority of doctors feel sufficient satisfaction regarding the work environment, but there is still room for improvement, especially regarding income commensurate with workload.